Transformation of Ministerial Performance Evaluation: Integrating Key Performance Indicators and Principles of Transparency into the Governance System - Saleh, Muhamad; Widiastuti, Retno (Journal of Constitutional and Governance Studies, 2025)
Presidentialism system emphasizes that president possess the authority to appoint and dismiss ministers, as stipulated in Article 17 of the 1945 Constitution of the Republic of Indonesia and the Law on State Ministries. However, this authority is often perceived as an absolute prerogative, lacking a clear mechanism for accountability. In a democratic system, the president’s power must inherently carry public responsibility, including in the appointment and dismissal of ministers. This study aims to analyze the problems in evaluating ministerial performance in Indonesia and how the integration of Key Performance Indicators (KPI) with the principle of public transparency can strengthen the accountability of ministerial governance. Currently, performance evaluation is conducted through the Government Agency Performance Accountability System (SAKIP), which relies heavily on internal reports from each ministry and lacks transparency and standardization. As a result, the evaluation process tends to be administrative, closed, subjective, limiting the public’s ability to assess ministerial performance comprehensively. Using a normative legal research method with statutory and conceptual approaches, this study focuses on integrating an objective, standardized, and transparent performance evaluation system. The findings emphasize the need for a comprehensive ministerial performance index grounded in public openness. The index as an objective basis for presidential decisions, including cabinet reshuffles, and enable public oversight. This study recommends the formulation of a specific regulation, such as a Presidential Regulation, to govern the standardized and transparent evaluation model, coordinated by the Cabinet Secretariat. Integrating KPIs and the principle of transparency will foster a more accountable, responsive, and democratic government.